International Public Sector Accounting Standards (IPSAS) and , Good Government Governance in Indonesia and Malaysia - Icih Icih; Putri Leonita Agustin; Asep Kurniawan; Mohammad H. Holle; Zumaroh Zumaroh (Sekolah Tinggi Ilmu Ekonomi Sutaatmadja, 2024)
Application of government accounting standards is one part of good government governance. Most countries in the world have realized the importance of applying international standards for accounting (IFRS) and auditing (ISA). This is done to show the country's role in the international community. Developments in the application of international standards in the private sector have not kept pace with developments in the public sector (IPSAS), including ASEAN countries. Human resources and supporting infrastructure is one of the problems faced by ASEAN countries in implementing IPSAS. Based on this, the purpose of this study is to determine the level of IPSAS disclosure in ASEAN government financial reports for the year ending 2019-2020.The exploratory quantitative method is the method used in this study with data analysis using descriptive statistics. Indonesia and Malaysia were selected as samples. Implementation of IPSAS disclosures in the 2019 by Indonesia State is 34% and Malaysia State is 29%. In 2020 IPSAS disclosure by the Indonesian State is 45% and Malaysia State is 30%. The results of the study show that although the application of IPSAS in Indonesia is greater than in Malaysia, in general IPSAS disclosure in these two countries still needs to be improved